Level of Work Motivation: A Descriptive Study Using the Work Motivation Scale on Employees in the Operational Unit of PT. Insurance X, Jakarta - Herawan, Budi; Rakhman, Sitti (Paspama Institute, 2025)
Work motivation is a key factor influencing employee performance within an organization. This study aims to describe the level of work motivation among operational employees at PT. Insurance X, Jakarta, in 2025. Using a quantitative descriptive method, data were collected through the Work Motivation Scale (WMS), consisting of 12 Likert-scale items (1–5). The study involved all 20 employees in the operational unit who agreed to participate. Results indicate a moderate level of work motivation, with an average score of 41.8, ranging from 38 to 46. The most influential dimension was intrinsic motivation, particularly job satisfaction and the desire for self-development. The findings suggest that employees are not yet fully driven to perform their tasks optimally. Therefore, strategic HR interventions are recommended, such as providing training opportunities, recognizing employee contributions, and reviewing bonus and promotion systems to enhance work motivation and job satisfaction.